The art of city sketching : a field manual - Abrams, Michael (Michael C.) (New York : Routledge, Taylor & Francis Group, 2014)
'The Art of City Sketching: A Field Manual guides you through the laborious and sometimes complex process of sketching what you see around you so that you can learn to draw what you imagine. Illustrated with hundreds of drawings by students and professionals of cityscapes around Europe and the United States, the book will help you develop your conceptual drawing skills so that you can communicate graphically to represent the built environment. Short exercises, projects, drawing tips, step-by-step demonstrations, and composition do's and don'ts make it easy for you to get out into the city and experiment in your own work'--
Keywords: Architectural drawing -- Technique